'TWIN SUN': A SIMPLE LUNAR ECLIPSE PREDICTOR. Issue 1 (12th June 2020) - Clausen, Claus
ABSTRACT: A simple method to predict lunar eclipses proposed in this article uses the position of the full moon relative to the sun. Calculations show that the method works better during the summer period in Scandinavia simply because the night is shorter and therefore the moon is closer to the exact time of the lunar eclipse when the moon rises as the sun is setting. When the conditions are right, the moon reflects the red colour of the setting sun. The two celestial bodies look within a short time as similar objects, like twins or 'Twin Sun' (TS). This article aims to demonstrate that TS is a useful method to predict lunar eclipses during the summer period at Northern latitudes. It will be discussed that TS as a lunar eclipse predictor could partly explain the alignment of some megalithic monuments in Denmark constructed from c. 3300‐3100 BC. Finally, it is suggested that TS could be an explanation behind the doubleness reflected in the construction of the Danish passage graves. Some archaeological finds seemingly also render the TS phenomenon.